Bromocriptine treatment in patients with peripartum cardiomyopathy and right ventricular dysfunction - Haghikia, Arash; Ehlermann, Philipp (Clinical research in cardiology, 2019)
BackgroundRight ventricular (RV) dysfunction predicts adverse outcome in peripartum cardiomyopathy (PPCM). We recently demonstrated beneficial effects associated with the prolactin release inhibitor bromocriptine at different doses when added to standard heart failure therapy in PPCM. Here, we evaluated for the first time the therapeutic potential of bromocriptine particularly in PPCM patients with RV involvement.MethodsIn this study, 40 patients with PPCM were included, of whom 24 patients had reduced RV ejection fraction (RVEF < 45%). We examined the effect of short-term (1W: bromocriptine, 2.5 mg, 7 days, n = 10) compared with long-term bromocriptine treatment (8W: 5 mg for 2 weeks followed by 2.5 mg for another 6 weeks, n = 14) in addition to guideline-based heart failure therapy in patients with an initial RVEF < 45% on the following outcomes: (1) change from baseline (Δ delta) in RVEF, (2) change from baseline in left ventricular EF (LVEF), and (3) rate of patients with full LV recovery (LVEF ≥ 50%) and (4) rate of patients with full RV recovery (RVEF ≥ 55%) at 6-month follow-up as assessed by cardiac magnetic resonance imaging.ResultsReduced RVEF at initial presentation was associated with a lower rate of full cardiac recovery at 6-month follow-up (patients with RV dysfunction: 58% vs. patients with normal RV function: 81%; p = 0.027). RVEF increased from 38 ± 7 to 53 ± 11% with a delta-RVEF of + 15 ± 12% in the 1W group, and from 35 ± 9 to 58 ± 7% with a Δ RVEF of + 23 ± 10% in the 8W group (Δ RVEF 1W vs 8W: p = 0.118). LVEF increased from 25 ± 8 to 46 ± 12% with a Δ LVEF of + 21 ± 11% in the 1W group, and from 22 ± 6 to 49 ± 10% with a Δ LVEF of + 27 ± 9% in the 8W group (Δ LVEF 1W vs 8W: p = 0.211). Full LV recovery was present in 50% of the 1W group and in 64% of the 8W group (p = 0.678). Full RV recovery was observed in 40% of the 1W group and in 79% of the 8W group (p = 0.092).ConclusionsDespite overall worse outcome in patients with RV dysfunction at baseline, bromocriptine treatment in PPCM patients with RV involvement was associated with a high rate of full RV and LV recovery, although no significant differences were observed between the short-term and long-term bromocriptine treatment regime. These findings suggest that bromocriptine in addition to standard heart failure therapy may be also effective in PPCM patients with biventricular impairment.